2019
DOI: 10.1176/appi.ajp.2019.18080957
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of Suicide Attempt in Psychiatric Disorders and Association With Major Depression Polygenic Risk Scores

Abstract: Objective: Over 90% of suicide attempters have a psychiatric diagnosis, however twin and family studies suggest that the genetic etiology of suicide attempt (SA) is partially distinct from that of the psychiatric disorders themselves. Here, we present the largest genome-wide association study (GWAS) on suicide attempt using major depressive disorder (MDD), bipolar disorder (BIP) and schizophrenia (SCZ) cohorts from the Psychiatric Genomics Consortium. Method: Samples comprise 1622 suicide attempters and 8786 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
203
7
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 218 publications
(232 citation statements)
references
References 38 publications
16
203
7
6
Order By: Relevance
“…The PRS-PCA approach controls Type I error while maintaining good power. This approach is well-suited to hypothesis testing with many PRSs, because it prevents overfitting each PRS to the outcome and does not require choosing one p-value threshold for all PRSs (Mullins et al, 2019;Richardson et al, 2019;Zheutlin et al, 2019), which can reduce power as seen in our simulations. In this study, we explored how the PRS-PCA approach can improve PRS analyses that implement P+T, by using the F I G U R E 2 Scaled weights on effect sizes of SNPs (betas) for SCZ-PRS assigned by PRS-PCA in the Mayo Clinic sample.…”
Section: Discussionmentioning
confidence: 99%
“…The PRS-PCA approach controls Type I error while maintaining good power. This approach is well-suited to hypothesis testing with many PRSs, because it prevents overfitting each PRS to the outcome and does not require choosing one p-value threshold for all PRSs (Mullins et al, 2019;Richardson et al, 2019;Zheutlin et al, 2019), which can reduce power as seen in our simulations. In this study, we explored how the PRS-PCA approach can improve PRS analyses that implement P+T, by using the F I G U R E 2 Scaled weights on effect sizes of SNPs (betas) for SCZ-PRS assigned by PRS-PCA in the Mayo Clinic sample.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] A genome-wide association study (GWAS) of suicidal thoughts and behaviour in MDD, indicated a polygenetic architecture with multiple genes implicated even though with small effects. 26 However, although several GWAS studies have been conducted on SA examining individuals with MDD, comparing suicide attempters with non-attempters and testing for genetic variants that might contribute independently to SA, [27][28][29][30][31] epidemiological evidence suggests that the inheritance of suicidality is likely to be independent of the underlying MDD, by supporting a distinct genetic contribution to suicidality. 32 Polygenic risk scores for SA have shown modest predictive capability in independent samples, and small but significant single-nucleotide polymorphism (SNP) heritability estimates for SA have been reported.…”
Section: Genetic Vulnerability and Epigenetic Modulationmentioning
confidence: 99%
“…The PRS-PCA approach was designed to control type I error while maintaining good power. This approach is most suited to hypothesis testing with many PRSs because it prevents overfitting each PRS to the outcome and does not require choosing one p-value threshold for all PRSs 8,9,25 , which can reduce power. In this paper, we explored how the PRS-PCA approach can improve PRS analyses that implement P+T.…”
Section: Discussionmentioning
confidence: 99%